Resonance of French Poetry in The Black Heralds - Gladieu, Marie-Madeleine (2020)
Without doubt romantic and modernist, Spanish and Hispanic American poets influenced César Vallejo, but reading poetry books from French authors of the XIXth century and beginning of the XXth, romantics, parnassians, symbolists, etc., certainly impacted the Peruvian poet. María Rosa Sandoval read in French for the group of young poets pieces of poetry from Baudelaire, Nerval, Verlaine, Samain, Laforgue, Mallarmé… Vallejo heard these texts, and read also other authors as we shall observe, especially «Un coup de dés», that awoke in his sensibility series of resonance proceeding from French sounds —cf. The music for Verlaine— that the poet interprets in his poems in different situations and imagery. Some examples of resonance remember Romanticism, avant-garde movements, other ones are more original and personal. Whatever many examples of pure sounds in Trilce seem to confirm that in the first poetry book, sounds and their resonance are important for César Vallejo’s poetic creation.